Exercise as Stroke Prophylaxis - Reimers, Carl-Detlef; Knapp, Guido; Reimers, Anne (Deutsches Ärzteblatt international, 2009)
Background: Stroke is the third most common cause of death in industrialized countries, accounting for more than 10% of deaths over age 65. Most strokes are due to arteriosclerosis. Regular physical activity lowers arterial blood pressure and body weight and improves glucose and lipid metabolism, thereby slowing the development of arteriosclerosis and its cardiovascular complications, particularly myocardial infarction. This review focuses on the question whether physical activity might also have a preventive effect on cerebral infarction and hemorrhage. Methods: This analysis is based on 33 prospective cohort studies and 10 case-control studies that addressed the potential effect of physical activity on stroke-related morbidity and mortality. Results: Our meta-analysis shows that physical activity reduces the risk of all types of stroke (infarction, hemorrhage, and stroke of unspecified type). The relative risk (RR) of fatal or non-fatal cerebral infarction is 0.75, while the corresponding figures for cerebral hemorrhage and stroke of unspecified type are 0.67 and 0.71, respectively. The reduction of risk is only statistically significant for men. The case-control studies show an RR of 0.32 for men and women combined. Conclusions: When a multivariate analysis is performed that takes other vascular risk factors into account, physical activity is found to have an independent protective effect against cerebrovascular events. The effect is statistically significant only for men, not for women.
Keywords: stroke; cerebral hemorrhage; risk of stroke; physical activity; health-related behavior